Drinking water: Costa Rica in the global context at the year 2017 - Mora-Alvarado, Darner A. (2019)
The present study aims to describe the progress on coverage and quality of drinking water in Costa Rica, and its comparison with American countries and the world. The concepts of Improved Drinking Water Sources used by the Joint Monitoring Programme for Water Supply (JMP) within the framework of the Millennial Development Goals and Safely Managed Drinking Water Service according to the Development Sustainable Goals were described and compared. The coverage and quality of drinking water in Costa Rica, given by the Laboratorio Nacional de Aguas (LNA), were described. According to the progress on Safely managed drinking water, data from Costa Rica and the world was compared. Also, the strategies of Costa Rica to accomplish with the universalization of drinking water services to 2022 and 2030 were described. The results showed that Costa Rica, according to the LNA, reached a 91.2% of safely managed drinking water, and a 90% according to the JMP. It’s essential to continue with the strategies driven by the LNA, which include: Water Safety Plans, the monitoring of water quality in homes, health centers and education centers. Lastly, it is recommended that the other regions of the world apply similar guidelines to those applied in Costa Rica to improve drinking water services.